The Influence of Apparatus Accountability on the Quality of Public Services in Kondara Village, Pakue District, North Kolaka District - Nanda Sari; H. Jamaluddin; Kamaruddin Sellang (International Journal of Sustainable Applied Sciences, 2024)
The Slovin formula was the sampling method employed, and 94 participants' data were obtained using a random sampling methodology. This kind of study is descriptive and quantitative. The methods of gathering data include questionnaires, library research, interviews, and observation. Using the IBM SPSS Statistics 22.00 application, validity, reliability, and simple linear regression tests are the data analysis techniques employed. The results of this research show that the accountability of officials at the Village Office is in a good category with percentage results of a) program accountability of 68%, b.) policy accountability of 64%, c) program accountability of 54%, d) legal accountability 63%, with an average percentage of 62%. The quality of public services at the Kondara Village office is in a good category with percentage results of a) direct evidence of 65%, b) reliability of 61%, c) responsiveness of 62%, d) guarantee of 61% e) empathy of 64% with an average percentage of 63 %. The influence of apparatus accountability on the quality of public services is 16.4% while the remaining is 83.6%. Based on the results of SPSS data processing using a simple linear regression formula, Ha is accepted and Ho is rejected, so that apparatus accountability affects public services in Kondara Village, Pakue District, North Kolaka Regency